APLIKASI ADI PARWA DALAM RELIEF SITUS CANDI KIDAL - Ni Nyoman Tanjung Turaeni (Forum Arkeologi, 2016)
Old Javanese literatures which are visualized into relief are in limited number few of them are the story of Partayadnya, Kunjarakarna, Arjuna Wiwaha, Adi Parwa and so on. This study aims to describe completely the structure and social phenomenon of Adi Parwa literature with wall relief at Kidal Temple Site. The analysis of this research describes descriptively with media changing approach, Adi Parwa literature into relief at Kidal temple. On the wall of Kidal Temple. There are three Garuda relief with different characteristic. All of those Garuda relief have close relation with parts of Adi Parwa.